Gases of coal fields: a new solution of the problem of synthesis–genesis of methane - Naumkо, I. М.; Pavlyuk, M. I.; Svoren, Yo. М.; Zubyk, M. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
The mainly abiogenic-biogenic genesis of methane of gas-coal fields is grounded on a new theory of synthesis and genesis of natural hydrocarbons — "abiogenic-biogenic dualism" — and a new physico-chemical model of the deep mineral- and naphthid-genesis in Earth's lithosphere. As far as the synthesis of methane together with other hydrocarbons in the medium of a deep high temperature fluid with the participation of abiogenic-biogenic sources is realized adiabatically in Earth's bowels (as a high energy physico-chemical reactor) in different geological periods, i. e. endlessly (!) in the geological calculus, this gives the foundation to assert the presence of their constant practically unexhaustible source. Hereby, the conception of the purely biogenic origin of methane of coal beds and coal-containing rocks, which denies a priori the possibility for its resources to be renewed, has been disproved.